Hierarchical Elemental Odor Coding for Fine Discrimination Between Enantiomer Odors or Cancer-Characteristic Odors - Sato, Takaaki; Matsukawa, Mutsumi; Iijima, Toshio; Mizutani, Yoichi (Frontiers in Behavioral Neuroscience, 2022)
Odors trigger various emotional responses such as fear to predator odors, aversion to disease or cancer odors, attraction to male/female odors, appetitive behavior to delicious food odors. Odor information processing for fine odor discrimination, however, has remained difficult to address. The olfaction and color vision share common features that G protein-coupled receptors are the remote sensors. As different orange colors can be discriminated by distinct intensity ratios of elemental colors yellow and red, odors are likely perceived as multiple elemental odors in a hierarchical manner that the intensities of elemental odors are in order of dominance. For example, in a mixture of rose and fox-unique predator odors, robust rose odor alleviates fear of mice to predator odors. Moreover, although occult blood odor is stronger than bladder cancer-characteristic odor in urine samples, sniffer mice can discriminate bladder cancer odor in occult blood-positive urine samples. In forced-choice odor discrimination tasks for pairs of enantiomers or pairs of body odors vs. cancer-induced body odor disorders, sniffer mice discriminated learned olfactory cues in a wide range of concentrations, where correct choice rates decrease in the Fechner's law, as perceptual ambiguity increases. In this mini-review, we summarize current knowledge of how the olfactory system encode and decode multiple elemental odors in a hierarchical manner to control odor-driven behaviors.